Synthesis and Characterization of New Azo isoxazole and pyrozole derivatives and Studies the biological activity - Rajaa Abd AL-Ameer Gafel (Al-Qadisiyah Journal of Pure Science, 2017)
Aseries of new substituted phenyl azo isoxazoline-5-one (d-f) and substituted phenyl azo pyrozoline-5-one (g-i) have been synthesized from the substituted phenyl azo pentan 2,4-dion (a-c).The Structure of all new compounds (a-i) were fullyidentifed by elemental analysis and FT.IR spectra but som of new compounds were chaarecterized by HNMR spectra,for the new compounds biological activity.Key word:isoxazoline-5-one,pyrozoline-5-one synthesis